Determinación y evaluación de contusiones en canales bovinas en un matadero de la región de Ñuble, Chile - Letelier Contreras, Reinaldo (2025)
The aim of this study was to relate the degree bruises in bovine carcass with the characteristics of the animals and the transport distance to a slaughterhouse in the Ñuble region, Chile, during the period November-December 2018. A total of 193 bovine carcasses were evaluated in which category, degree of bruises, sex, weight, and locality of origin were identified. Data showed that 76.2% (147/193) of the carcasses corresponded to males and 23.8% (46/193) to females. A total of 152 contusions were observed, being mainly grade 1 in 55.4% (107/193), followed by 21.8% (42/193) grade 2 and only 1.6% in grade 3 (3/193), while 21.2% (41/193) of the carcasses were free of contusions. Besides, 83.4% (161/193) of carcasses corresponded to category V. The largest number of animals (76.8%) came from distances of less than 60 km. There was no association between the distance of travel and the presence of bruises (p>0.05). However, although transport distance was not an influential factor in the appearance of bruises, sex (female) and greater weight separately were more prone to the appearance of bruises (p<0.05).